1974
DOI: 10.1073/pnas.71.9.3405
|View full text |Cite
|
Sign up to set email alerts
|

The Pancreatic β-Cell Recognition of Insulin Secretagogues: Does Cyclic AMP Mediate the Effect of Glucose?

Abstract: Insulin release and the content of cAMP were studied in microdissected pancreatic islets of noninbred ob/ob (obese) mice. In the absence of 3-isobutyl-1-methylxanthine, a phosphodiesterase inhibitor, 20 mM glucose had no effect on cAMP save a very small initial rise detectable by a freeze-stop perifusion technique only. However, combined with this methylxanthine, 20 mM glucose produced significant increases of cAMP both in perifused islets and in islets conventionally incubated in closed vials. Glucose shared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 22 publications
5
62
0
Order By: Relevance
“…The present experiments demonstrated that glucose stimulation of islets produced marked elevation of cAMP levels, a result also reported by Charles et al [8], by Selawry et al [10] by Grill and Cerasi [9,12] as well as by Capito and Hedeskov [14] but not confirmed by Cooper, Ashcroft and Randle [16] and Hellman et al [17]. Reasons for these discrepancies are not readily apparent, but subtle differences in the procedures for isolating pancreatic islets with crude collagenase used by the several laboratories, species differences, or the nutritional state of the animal [14] seem to be the most likely causes.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The present experiments demonstrated that glucose stimulation of islets produced marked elevation of cAMP levels, a result also reported by Charles et al [8], by Selawry et al [10] by Grill and Cerasi [9,12] as well as by Capito and Hedeskov [14] but not confirmed by Cooper, Ashcroft and Randle [16] and Hellman et al [17]. Reasons for these discrepancies are not readily apparent, but subtle differences in the procedures for isolating pancreatic islets with crude collagenase used by the several laboratories, species differences, or the nutritional state of the animal [14] seem to be the most likely causes.…”
Section: Discussionsupporting
confidence: 76%
“…It remains an open question whether insulin release resulting from glucose, the major physiological B-cell stimulus, involves elevation of cAMP levels as an obligatory step. In several studies it was found that cAMP was elevated in isolated pancreatic islets exposed to high glucose [8--14]; however in an equally large number of papers it was reported that glucose alone did not alter the cAMP levels of islet tissue [15,16] or had only a small transient effect [17[.-Some have found that high glucose elevated cAMP when a phosphodiesterase inhibitor was present [8,9,17] others, however, did not confirm this phenomenon [15,16]. This is a report of some of the results we have obtained in an effort to help clarify the issue.…”
mentioning
confidence: 99%
“…cAMP is formed by adenylyl cyclases in response to G s -coupled receptor agonists, such as glucagon, the incretin hormones glucagon-like peptide-1 (GLP-1) and gastric inhibitory popypeptide (GIP), as well as the neuropeptides pitutitary adenylate cyclase activating polypeptide (PACAP) and vasoactive intestinal popypeptide (VIP). Also glucose-stimulated islets show a modest elevation of cAMP (Charles et al, 1973;Grill and Cerasi, 1973;Hellman et al, 1974;Sharp, 1979), an effect that has been attributed to the elevation of [Ca 2+ ] i (Charles et al, 1975;Valverde et al, 1979). From the observation that purified β-cells, lacking influence from the glucagon-producing α-cells, show reduced cAMP content and impaired secretory capacity, it was suggested that cAMP has a permissive role in glucose-induced insulin release and that the effect of the sugar on cAMP content represents amplification of glucagon-induced cAMP production (Schuit and Pipeleers, 1985).…”
Section: Cyclic Ampmentioning
confidence: 99%
“…These results indicate that a specific block of glucose utilization is not responsible for the observed inhibition. Although cyclic AMP probably does not mediate glucose induced insulin release [22], it is widely accepted that the nucleotide potentiates the effects of glucose and other stimulators [23]. Thus the potentiating effect of theophylline on glucose-induced insulin release may be mediated by an increase of the intracellular cyclic AMP [24], which in turn was supposed to translocate calcium from organelle-bound pools to the cytoplasm [25].…”
Section: Discussionmentioning
confidence: 99%